The surprise party - Bradman, Tony.; Chatterton, Martin (London : Egmont UK, 2004)
When members of the Mummy family decide to have a surprise party for Grand-daddy and Grand-mommy Mummy, their plans do not work out exactly as expected.
3.5
K-3.
K-3
Keywords: Grandparents -- Juvenile fiction; Mummies -- Juvenile fiction; Grandparents -- Fiction; Humorous stories; Mummies -- Fiction; Grandparents -- Fiction; Humorous fiction; Mummies -- Fiction; Humorous fiction; Readers (Elementary).